Seasonal Variability of Mesozooplankton Feeding Rates on Phytoplankton in Subtropical Coastal and Estuarine Waters - Chen, Mianrun; Liu, Hongbin; Chen, Bingzhang (Frontiers in Marine Science, 2017)
In order to understand how mesozooplankton assemblages influenced phytoplankton in coastal and estuarine waters, we carried out a monthly investigation on mesozooplankton composition at two contrasting stations of Hong Kong coastal and estuarine waters and simultaneously conducted bottle incubation feeding experiments. The assemblage of mesozooplankton was omnivorous at both stations with varying carnivory degree (the degree of feeding preference of protozoa and animal food to phytoplankton) and the variations of carnivory degree were significantly associated with microzooplankton biomass (ciliates for the coastal station, both ciliates and dinoflagellates for the estuarine stations) and physical environmental parameters (primarily salinity). High carnivory was primarily due to high composition of noctilucales, Corycaeus spp., Oithona spp. and Acartia spp. Results of feeding experiments showed that grazing impacts on phytoplankton ranged from -5.9% to 17.7%, while the mean impacts were just less than 4% at both stations. The impacts were size-dependent, by which mesozooplankton consumed around 9% of large-sized phytoplankton while indirectly caused an increase of 4% of small-sized phytoplankton. Mesozooplankton clearance rate on phytoplankton, calculated from the log response of chlorophyll a concentrations by the introduction of bulk grazers after one-day incubation, was significantly reduced by increasing carnivory degree of the mesozooplankton assemblage. The mechanism for the reduction of mesozooplankton clearance rate with increasing carnivory degree was primarily due to less efficient of filtering feeding and stronger trophic cascades due to suppression of microzooplankton. The feeding rates of mesozooplankton on microzooplankton were not obtained in this study, but the trophic cascades indirectly induced by mesozooplankton carnivorous feeding can be observed by the negative clearance rate on small-sized phytoplankton. Overall, the main significance of this study is the empirical relationship between carnivory degree and clearance rate, which allow researchers to potentially predict the herbivory of mesozooplankton in the nature without conducting feeding experiments.